Effect of new Aliens Act of Finland on the fair trial in asylum cases - Jatoi, Mir Nasarullah Khan (Riga Graduate School of Law, 2020)
This thesis describes various elements of the rights to fair trial, free access to the justice, fairness, public hearings, and trials by the independent tribunals. The purpose of this thesis is to examine new Aliens Act Amendment Act 646/2016 of Finland, which is believed not entirely respect certain human rights such as some fair trial guarantees. Here, Finland violates the EU Directive 2013/32/EU by way of changing the asylum procedure directive and incorporating them into the domestic law, but it was implemented from July 2018. The legal analysis focuses on the new amendments where the courts can make the decisions without having the evidence in the cases of asylum and limiting the time for the appeals. Furthermore, decreasing the legal aid, which is leading the violation of free access to justice, these changes are the most likely effect on the right to the fair trial. The legal analysis will suggest that what could be the suitable asylum process which should comply with the asylum procedure Directive 2013/32/EU and the authorities need to act speedily to correct wrongful decisions of Asylum requests. As a basis of analysis, author has collected and analysed various primary as well as secondary sources of information, including ECtHR judgments, Finnish laws, contemporary literature, other publications from International and Finish institutes and governmental organisations. In order to view the consequences of Aliens Act Amendment Act 646/2016, on the right to a fair trial, the doctrinal research methodology has been used and the study of various cases, which has been analysed and discussing how this new act 646/2016 has been evolved because of current issues concerning asylum seekers.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights; Finland